Manufacturing of Perovskite Oxygen Carriers by Spray Granulation for Chemical Looping Combustion. Issue 11 (12th September 2017) - Thoréton, Vincent; Darell, Ove; Spjelkavik, Aud I.; Sunding, Martin Fleissner; Mokkelbost, Tommy; Pishahang, Mehdi; Wiik, Kjell; Larring, Yngve
Abstract: Chemical looping combustion is a technology under development that allows power production with inherent separation of CO2 during fuel combustion. Its principle relies on oxygen carrier materials transporting oxygen from air to oxidize the fuel. One challenge is to develop and produce materials with suitable chemical and physical properties, as well as low environmental impact, while minimizing the cost of production. Herein, it is demonstrated that spray granulation, which is a scalable industrial process, is relevant for the manufacture of promising oxygen carrier materials from low‐cost, low‐environmental‐impact minerals and with good mechanical properties: Ca0.98 Mn0.875 Ti0.125 O3 and Ca0.98 Mn0.75 Fe0.125 Ti0.125 O3 . Iron substitution clearly reduces the sintering time. Increasing the calcination temperature and calcination time enhances the bulk density and resistance against physical attrition. Abstract : Creating carriers : Spray granulation is a scalable industrial process that is relevant for the manufacture of promising oxygen carrier materials for chemical looping combustion from low‐cost, low‐environmental‐impact minerals with good mechanical properties.